A randomized, double‐blind, crossover, placebo‐controlled trial of 6 weeks benfotiamine treatment on postprandial vascular function and variables of autonomic nerve function in Type 2 diabetes. Issue 10 (12th June 2013) - Stirban, A.; Pop, A.; Tschoepe, D.
Abstract Aims In a pilot study we suggested that benfotiamine, a thiamine prodrug, prevents postprandial endothelial dysfunction in people with Type 2 diabetes mellitus. The aim of this study was to test these effects in a larger population. Methods In a double‐blind, placebo‐controlled, randomized, crossover study, 31 people with Type 2 diabetes received 900 mg/day benfotiamine or a placebo for 6 weeks (with a washout period of 6 weeks between). At the end of each treatment period, macrovascular and microvascular function were assessed, together with variables of autonomic nervous function in a fasting state, as well as 2, 4 and 6 h following a heated, mixed test meal. Results Participants had an impaired baseline flow‐mediated dilatation (2.63 ± 2.49%). Compared with the fasting state, neither variable changed postprandially following the placebo treatment. The 6 weeks' treatment with high doses of benfotiamine did not alter this pattern, either in the fasting state or postprandially. Among a subgroup of patients with the highest flow‐mediated dilatation, following placebo treatment there was a significant postprandial flow‐mediated dilatation decrease, while this effect was attenuated by benfotiamine pretreatment. Conclusions In people with Type 2 diabetes and markedly impaired fasting flow‐mediated dilatation, a mixed test meal does not further deteriorate flow‐mediated dilatation or variables of microvascular or autonomic nervous function. Because no significant deterioration of postprandial flow‐mediated dilatation, microvascular or autonomic nervous function tests occurred after placebo treatment, a prevention of the postprandial deterioration of these variables with benfotiamine was not feasible.